2019
DOI: 10.3389/fpls.2019.00375
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Analysis of MBW Function by Phenotypic Rescue in Arabidopsis thaliana

Abstract: The MBW complex consisting of the three proteins R2R3 M YB, b HLH and W DR regulates five traits in Arabidopsis thaliana including trichome and root hair patterning, seed coat color, anthocyanidin production and seed coat mucilage release. The WDR gene TTG1 regulates each trait in specific combinations with different bHLH and R2R3MYB proteins. In this study we analyze to what extent the biochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 65 publications
(104 reference statements)
1
15
0
Order By: Relevance
“…For example, the meristem identity transition transcription factor gene, LMI2 (Pastore et al, 2011), resides near a DHS that was deactivated during seed coat cell maturation ( Figure 1B ). Similar to previous observations (Sullivan et al, 2014), the majority of observed DHSs were static during development, such as those flanking TTG1 , which encodes a WDR protein that regulates seed coat mucilage release (Zhang and Hülskamp, 2019) ( Figure 1B ). The regulatory landscape of seed coat cells differed significantly from the landscape of root nonhair cells, another epidermal cell type, as well as from whole roots ( Figures 1B and 5 ).…”
Section: Resultssupporting
confidence: 88%
“…For example, the meristem identity transition transcription factor gene, LMI2 (Pastore et al, 2011), resides near a DHS that was deactivated during seed coat cell maturation ( Figure 1B ). Similar to previous observations (Sullivan et al, 2014), the majority of observed DHSs were static during development, such as those flanking TTG1 , which encodes a WDR protein that regulates seed coat mucilage release (Zhang and Hülskamp, 2019) ( Figure 1B ). The regulatory landscape of seed coat cells differed significantly from the landscape of root nonhair cells, another epidermal cell type, as well as from whole roots ( Figures 1B and 5 ).…”
Section: Resultssupporting
confidence: 88%
“…In addition to the regulation of the flavonoid pathway, genes of the regulatory complex MBW are also responsible for a number of functions in the plant organism [52], for example, such as the formation of spines analyzed by us [27]. Therefore, the MBW genes, especially bHLH and MYB, are highly variable [47].…”
Section: Discussionmentioning
confidence: 99%
“…As indicated in the name, MBW, the complex is generally comprised of three distinguished transcription factors including MYB, bHLH and WDR [reviewed in Xu et al., ]. Based on the characterizations of different Arabidopsis mutants at phenotypic, genetic and molecular levels, the MBW complex is known to regulate two groups of traits in this model plant including: (1) plant tissue colour (anthocyanin biosynthesis and seed coat colour) and (2) epidermal cell fate determination (root hair and trichome morphogenesis) [Zhang and Hulskamp, ; Shibata and Sugimoto, ]. In Arabidopsis, MYB is a large gene family which contains more than 180 members [Yanhui et al., ; Dubos et al., ; Nguyen et al., ].…”
Section: Mbw Complexmentioning
confidence: 99%
“…The bHLH transcription factors can be TRANSPARENT TESTA8 (TT8), GLABROUS3 (GL3), ENHANCER OF GLABRA3 (EGL3) or MYC1 [Zhang et al., ; Baudry et al., ; Gou et al., ; Pesch et al., ]. Although there are several MYB and bHLH transcription factors in each group, the WDR is only encoded by one single copy gene, TRANSPARENT TESTA GLABRA1 ( TTG1 ) [Koornneef, ; Nguyen et al., ; Zhang and Hulskamp, ]. The DNA‐binding proteins (MYB and bHLH) together with TTG1 comprise a tertiary transcription factor complex which can generally activate the downstream genes to regulate the mentioned traits in Arabidopsis plant [Xu et al., ; Miller et al., ; Zhang and Hulskamp, ].…”
Section: Mbw Complexmentioning
confidence: 99%